Evaluation of RISE: A Sexual Violence Prevention Program for Female College Students in India - Nieder, Christina (Journal of interpersonal violence, 2022)
RISE, a sexual violence prevention program for female college students in India, covers topics on gender, healthy relationships, sexual violence, and bystander education, and focuses on the teaching of knowledge, the promotion of positive attitudes as well as the support of effective behaviors to prevent sexual violence against women in India. However, it is yet unclear what impact this program has in preventing sexual violence. In this evaluation study, a total of N = 245 female college students based in New Delhi and aged 17 to 22 years were assigned to a training (N = 128) or a waitlist control group (N = 117). The prevention program was conducted by two Indian professionals of a non-governmental organization (NGO) in New Delhi within five sessions. Results indicated that students in the training group showed significant increases in awareness of gender stereotypes, the importance of communication in relationships, bystander efficacy as well as intentions to intervene as a bystander in situations of violence when compared to students in the control group right after the program (posttest) and six months later (follow-up). Additionally, the training group displayed a significant increase of knowledge in all four program areas (gender, healthy relationships, sexual violence, and bystander education). Our findings implicate that future sexual violence prevention programs in India need to address women as well as men to effectively tackle sexual violence. In this context, bystander education seems to be one of the most promising approaches by targeting whole communities and creating new social norms regarding helping behavior and the prevention of sexual violence.